Organizational Support, Mustahiq Micro-Business Development and Poverty Alleviation: A Comparison Analysis Between BAZNAS and LAZNAS - Budi Trianto; Evan Hamzah Muchtar; Ade Chandra; Masrizal Masrizal; Tasiu Tijjani Sabiu (Faculty of Islamic Economics and Business of UIN K.H. Abdurrahman Wahid Pekalongan, 2021)
This study aims to investigate whether the organizational support provided by BAZNAS and LAZNAS has a positive impact on the success of micro business development programs and poverty alleviation. The population in this study are mustahiq who have received an empowerment program from BAZNAS and LAZNAS with a total sample size are 89 mustahiq. Data were collected using a questionnaire with a Likert scale of 1 – 5 and were analyzed using Path Analysis. The results of this study indicate that the organizational support provided by LAZNAS tends to be better when compared BAZNAS. This study also found an important fact that the mustahiq micro-business development program was able to alleviate poverty. The results of this study imply that to get a maximum result of mustahiq micro-business development, BAZNAS must evaluate and innovate the mustahiq micro-business development program. Meanwhile, LAZNAS must provide more optimum support for capital assistance and mentoring to get a maximum impact. This is the first study in comparing the micro-business development between BAZNAS and LAZNAS in Indonesia.